IDENTIFIKASI PRIORITAS PEMBENAHAN KINERJA KEJADIAN RISIKO OPERASIONAL KEBUN RAYA CIBODAS BERLANDASKAN TEMUAN PERANGKAT DETEKSI - Sugiarto, Sugiarto; Wahjudi, Januar; Nursiana, Adinoto; Budhijono, Fongnawati; Sutrisno, Sutrisno (Jurnal Bina Manajemen, 2023)
The rapid changes in developments in many aspects recently have made the role of operational risk management in the Cibodas Botanical Gardens very strategic. For this purpose, various detection tools are needed that enable the management of the Cibodas Botanical Gardens to trace various risk events, especially those that have significant impact on visitors, and based on these findings, the management can design various relevant operational risk management strategies and its implementation. This research is based on mixed research methods, using cross section data taken using the Concurrent Triangulation Strategy technique from 560 tourists and key informants at the Cibodas Botanical Gardens. Various detection tools used in this research include Frequency Tables, Bar charts, Pareto Diagrams, Cause and Effect, Importance-Performance Analysis, and Expectation and Perception Difference tests. The research results found that there was a synergy of various detection devices used in tracing various risk events which in order of priority had significant impact on tourists, namely Doctors on Duty, Adequate number of officers, Suggestion boxes, Management Innovation, Polyclinics, Toilets, Published information, Manpower, Quality of workforce, Helpful service, Parking space, Availability of information, and Prompt service.